2019
DOI: 10.3892/mmr.2019.9872
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of melatonin receptors 1A and 1B may result in disordered lipid metabolism in obese patients with polycystic ovary syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a condition in which a woman's levels of the sex hormones (estrogen and progesterone) are out of balance, leading to the growth of ovarian cysts. PCOS can affect the menstrual cycle, fertility, cardiac function and even appearance of women. Therefore, we aimed to explore the genetic polymorphism of the melatonin receptors 1A and 1B in obese patients with PCOS to identify a new theoretical basis for its treatment. Patients presenting with PCOS (n=359) were enrolled and classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
8
1
1
Order By: Relevance
“…We compared the level of obesity and serum melatonin levels. Our study revealed that people with obesity grades I and II have low melatonin levels, but the differences were not statistically significant …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We compared the level of obesity and serum melatonin levels. Our study revealed that people with obesity grades I and II have low melatonin levels, but the differences were not statistically significant …”
Section: Discussioncontrasting
confidence: 73%
“…In another study, researchers sought to study the genetic polymorphism of melatonin receptors 1A and 1B in obese patients with polycystic ovarian syndrome (PCOS) to identify a new theoretical basis for its treatment. As a result, the study provided evidence of the relationship between the polymorphism of the melatonin receptor genes and lipid metabolism disorders in patients with PCOS …”
Section: Discussionmentioning
confidence: 83%
“…Its etiology and pathogenesis are related not only to genetic factors, but also to environmental factors [3–6]. Recent studies have shown that the etiology of PCOS is likely correlated with genes involved in androgen elevated, insulin resistance and insulin-regulating genes, as well as those involved in metabolism, steroid hormones and glandular hormone biosynthesis [7–10].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, evidence has been provided showing the relationship between rs2119882 and rs10830963 melatonin receptor polymorphism and lipid metabolism disorder in PCOS patients, highlighting the importance of the therapeutic and protective effects of melatonin and its metabolites [ 16 ].…”
Section: Introductionmentioning
confidence: 99%